Regulatory T cell therapy promotes TGF-β and IL-6-dependent pro-inflammatory Th17 cell generation by reducing IL-2 - Hao Cheng; Fang Nan; Ning Ji; Xiao Ma; Jianan Zhang; Hantian Liang; Wei Zhang; Hiroko Nakatsukasa; Huiyuan Zhang; Wenwen Jin; Hong Jiang; Jiyu Tong; et al. (Nature Communications)
Abstract CD4+Foxp3+ regulatory T cells are essential for maintaining immune tolerance and preventing excessive inflammation, making them promising candidates for treating autoimmunity and GvHD. However, the translation of regulatory T cell therapy into clinical practice poses substantial challenges. Here, we show that adoptive regulatory T cell therapy increases IL-6 and TGF-β-dependent pathogenic Th17 cell differentiation in murine models of inflammatory bowel disease and experimental autoimmune encephalomyelitis. Regulatory T cells increase the p-stat3/p-stat5 ratio in effector T cells by suppressing IL-2 secretion and competitively consuming IL-2, thereby promoting Th17 cell differentiation. Notably, IL-2 signaling deficiency not only promotes a Th17 cell-associated transcriptional program, but also enhances the pro-inflammatory properties of Th17 cells. Strikingly, therapeutic blockade of IL-6/STAT3 signaling pathway can reverse pathogenic Th17 cell differentiation and enhance the therapeutic effect of regulatory T cell therapy. Thus, our findings could potentially advance the clinical research progress of adoptive regulatory T cell therapy.